The Impact of Shrouded Fees: Evidence from a Natural Experiment in the Indian Mutual Funds Market - Anagol, Santosh; Kim, Hugh Hoikwang (American Economic Review, 2012)
We study a natural experiment in the Indian mutual funds sector that created a 22-month period in which closed-end funds were allowed to charge an arguably shrouded fee, whereas open-end funds were forced to charge entry loads. Forty-five new closed-end funds were started during this period, collecting $7.6 billion US, whereas only two closed-end funds were started in the 66 months prior to this period, collecting $42 billion US, and no closed-end funds were started in the 20 months after this period. We estimate that investors lost and fund firms gained approximately $350 million US due to this shrouding. JEL: D14, G23, G28, O16